Tantric Yoga in the Mārkaṇḍeya Purāṇa of Hinduism and the Jñānārṇava of Jainism - Chapple, Christopher Key (Religions, 2017)
This paper explores the Markaṇḍeya Purāṇa, one of the earliest expositions of what become Tantric themes in Hinduism, and the Jñānārṇava, which provides an early template for the practice of Jaina Tantra. The former text follows the traditional mapping of the five elements and correlative senses, linking earth to smell, water to taste, fire to form, air to touch, and space to hearing, in a sequence of ascent. In contrast, the Jaina practice relates earthy, lotus-like material to the earth, to be incinerated by fire, stirring up strong winds that involve vigorous breathing that bring pounding rains, washing away all karmic impurity and its residues, exposing one’s true nature as a distinct liberated soul.